Mid Trimester Termination of Pregnancy : Role of Combined Mifepristone and Misoprostol (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Mid trimester abortions constitute 10%-15% of all induced abortionsworld wide. Over the last decade this increase is due to better prenatal screening. Itcan be done by surgical and medical methods. Medical methods such as Misoprostolis widely used for mid trimester abortion. Mifepristone has antiprogesteroneproperty,so addition of Mifepristone with Misoprostol can increase its effectiveness.To assess the safety, effectiveness and acceptibility of combined Mifepristone andMisoprostol for mid trimester medical termination of pregnancy (Between 13-24weeks of gestation).Materials and methods: This experimental study was conducted among 40 healthywomen who presented for mid trimester termination of pregnancy between 13-24weeks with missed abortion, gross congenital anomalies with or without previoushistory of one caesarian section. The study was conducted from March October2018 at Chattogram Maa-O-Shishu Hospital Medical College, Chattogram,Bangladesh. Each woman received a single dose of tablet Mifepristone 200mg. After24 hours, 200 mcg vaginal Misoprostol was administered which was repeated at 6hourly interval for maximum of 5 doses (1000 mcg) in 24 hours. Success was takenas complete expulsion of fetus and placenta within 24 hours of first dose ofMisoprostol. Primary and secondary outcomes were measured. Statistical analysiswas done using SPSS version 23.Results: Success rate of complete abortion was 97.5%. Mean Induction AbortionInterval was11.59 hours (SD± 3.34). Mean dose of Misoprostol was 1.85 (SD± 0.77)or 370 mcg. Over all safety of the study was satisfactory with only 1 patientexperienced fever and 1 had nausea .There was no major complication.Conclusion: The Mifepristone/Misoprostol regimen is a highly effective as well assafe option for mid trimester medical termination of pregnancy with a shortinduction abortion interval and it can also be used in scarred uterus with closesupervision.Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 63-67